2014
DOI: 10.2217/nnm.14.80
|View full text |Cite
|
Sign up to set email alerts
|

Wide-Field Multiplexed Imaging of EGFR-Targeted Cancers Using Topical Application of NIR SERS Nanoprobes

Abstract: This advancement represents a key step towards sensitive wide-field Raman endoscopic imaging of multiple biomarkers for early and accurate diagnosis of EGF receptor-expressing tumors of different internal organs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 36 publications
1
42
0
Order By: Relevance
“…In fact, it has been demonstrated that SEPs can adhere to tumor tissues in less than minutes, although the nonspecifically adsorbed SEPs must be removed by washing the tissue with serum (Wang et al 2014a). The obstacle set by the high background distribution of non-specifically bound nanoparticles can be overcome by implementing ratiometric approaches where one of the SEP type in the particle cocktail is used as a nonspecific internal reference to visually enhance the preferential adhesion of other targeting nanoparticles on tumor tissues (Mallia et al 2015;Oseledchyk et al 2017;Pallaoro et al 2011). Implementation of these methods is rather straightforward for SERS imaging due to the high degree of multiplexing provided by the narrow Raman linewidths.…”
Section: Sep Characterization Of Tumor Tissuesmentioning
confidence: 99%
See 4 more Smart Citations
“…In fact, it has been demonstrated that SEPs can adhere to tumor tissues in less than minutes, although the nonspecifically adsorbed SEPs must be removed by washing the tissue with serum (Wang et al 2014a). The obstacle set by the high background distribution of non-specifically bound nanoparticles can be overcome by implementing ratiometric approaches where one of the SEP type in the particle cocktail is used as a nonspecific internal reference to visually enhance the preferential adhesion of other targeting nanoparticles on tumor tissues (Mallia et al 2015;Oseledchyk et al 2017;Pallaoro et al 2011). Implementation of these methods is rather straightforward for SERS imaging due to the high degree of multiplexing provided by the narrow Raman linewidths.…”
Section: Sep Characterization Of Tumor Tissuesmentioning
confidence: 99%
“…While active targeting methods have proven to significantly reduce the dissipation of SEPs to healthy tissues and organs with respect to passive approaches, still toxicity and clearance issues remain major concerns associated with the systemic route of administration (such as via intravenous injections). Thus, when allowed, alternative strategies to circumvent these problems have been exploited, including topical spray-like applications (Mallia et al 2015;Zavaleta et al 2013) and direct intratumoral injections (Dinish et al 2014;Oseledchyk et al 2017).…”
Section: Systemic Vs Topical/local Administrationmentioning
confidence: 99%
See 3 more Smart Citations